Apocalyptic Time - Baumgarten, Albert I. (Numen Book Series, 2000)
Millennial movements are characterized by their nature and perception of time, and the ways in which these groups confront inevitable disappointment and then return to "normal" time. This is the theme for the book Apocalyptic Time . The volume consists of revised essays based on presentations made at an international conference devoted to that theme. Authors adopt a number of disciplinary approaches to the topic, analyzing millennial movements from the three Abrahamic faiths, as well as from the East. This book will be of particular interest to students of millennial movements, who wish to benefit from the comprehensive and comparative view it gives of the phenomenon, based on a wide variety of cases. This work greatly contributes to the theory of millennialism, by supplying specific data and theoretical reflection.